Goethe 2000 : intercultural readings of his work : papers presented at the University of Glasgow's Centre for Intercultural Germanistics, 19-21 April 1999 /: intercultural readings of his work : papers presented at the University of Glasgow's Centre for Intercultural Germanistics, 19-21 April 1999. (2017) - Unknown
No abstract available